Teaching Civilization to Enhance the Critical Thinking of EFL Students A case of Third Year LMD Students at Amar Telidji university- Laghouat- - BEN OUARITH, Saida; MEDJADI, Aicha; Ben REDDA ,Djamel (Faculty of Letters and Foreign Languages Department of English, 2019)
It is generally emphasized that critical thinking pedagogy plays a fundamental role in education and as a result, it needs to be integrated within the framework of civilization courses. For the process of critical thinking to occur, civilization teachers are required to adopt learner-centered methods of teaching that help EFL students to analyze, interpret, synthesis and evaluate what they are learning. Therefore, the current study aims at investigating the effect of teaching civilization on the critical thinking skills of EFL students, and to discover whether civilization is taught on the basis of this pedagogy in an effort to provide understanding about the main methods, techniques, and tools that have the potential to promote students’ critical thinking abilities. Most importantly, in order to gather the data necessary for this research, one main research instrument is at the heart of this investigation which is concerned mainly with two questionnaires handed to six civilization teachers, and to thirty four EFL students who belong to third year LMD classes at the university of Amar Thelidji (Laghouat). Accordingly, the suitable method for this research work is descriptive interpretive that combine quantitative and qualitative data. In here, mixed method is used in order to add validity to the research’ main findings. The analyses of both questionnaires results indicate that the majority of civilization teachers are aware of the importance of critical thinking in which they apply several methods, and techniques that can enhance the students’ ability to think critically, yet some students show negative attitudes towards this module. This leads us to offer some pedagogical implications that would enhance the quality of learning, and therefore, promote students’ critical thinking abilities.